Pomanjkanje vitalnosti slovenskega podjetništva: GEM Slovenija 2014 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja; Širec, Karin; Bradač Hojnik, Barbara; Rus, Matej (University of Maribor Press, 2015)
Lack of Slovenian Entrepreneurship Vitality : GEM Slovenia 2014. The times of crisis call for even more careful deliberation than usual about the steps which are necessary to take in order to use the existing resources and meet the needs to the maximum degree, which is impossible to do without energetic and dynamic entrepreneurship. Harmonized data provided by Global Entrepreneurship Monitor (GEM) have enabled us to better understand the place of Slovenian entrepreneurship within the global framework. The vitality of entrepreneurship thus cannot be determined by merely counting the number of businesses and entrepreneurs, but rather by learning about the entrepreneurial environment, the core characteristics of entrepreneurial activity, their motivations and ambitions. These dimensions of entrepreneurship are at the centre of research of GEM, the largest global research in the field of entrepreneurship, which has offered a detailed insight into the world of entrepreneurship for the past sixteen years. Quite a lot of attention is also devoted to the entrepreneurship ecosystem as it can significantly enhance (or hinder) entrepreneurial processes and activity.